A review on nanofiber fabrication with the effect of high-speed centrifugal force field - Zhang, Zhi-Ming; Duan, Yao-Shuai; Xu, Qiao; Zhang, Biao (Journal of engineered fibers and fabrics, 2019)
Among the traditional methods for nanofiber fabrication, their inherent defects limit their application in industry. This work presents a simple and novel spinning technology to fabricate nanofiber, which uses a high-speed rotary spinneret called high-speed centrifugal spinning. Unlike electrospinning, the electric field is not required, and it could fabricate nanofiber in bulk from melt or solution materials. This work introduces the mechanism principle and development of high-speed centrifugal spinning. Besides, the high-speed centrifugal spinning is compared with the traditional spinning methods. The jet movement and nanofiber formation process under the action of centrifugal force are explained in detail. The effects of equipment parameters and spinning solution parameters on final nanofiber morphology are presented. These parameters are controllable, they include rotational speed of spinneret, length and diameter of nozzle, spinning solution concentration, spinning solution viscosity and surface tension, and collection distance.